CHEMOKINE RECEPTORS AT DISTINCT DIFFERENTIATION STAGES OF T-HELPERS FROM PERIPHERAL BLOOD - I. V. Kudryavtsev; A. G. Borisov; I. I. Krobinets; A. A. Savchenko; M. K. Serebriakova; Areg A. Totolian (Медицинская иммунология)
Expression of chemokine receptors (CCR4, CCR6, CXCR3 and CXCR5) on T-helper (Th) cells at various levels of differentiation in a group of healthy volunteers (n = 52) was assessed on the basis of CD45RA and CD62L expression, using the eight-color flow cytometry. It was found that the “naive” T helper cells (N) with CD45RA+CD62L+ phenotype express CXCR3 (4.94±0.39%), and CXCR5 (3.63±0.25%). About 50% of central memory T helpers (CD45RA–CD62L+, CM) were CXCR3 positive, and 43.72±1.27% of CM cells expressed CCR6, whereas CXCR5 and CCR4 levels were about 30%. Furthermore, CXCR3 was expressed by 76.76±0.75% of the CD3+CD4+CD45RA–CD62L– (EM) population, and similar values were obtained for CCR6, while the relative abundance of CXCR5+ cells decreased to 13.68±0.50%, and CCR4 levels did not change and accounted for 33.26±1.13% positive cells. Likewise, co-expression of the chemokine receptors was studied for the abovementioned subpopulations of T helper cells. Among the CXCR5– Th, Th1 cells were identified as CXCR3+CCR6–CCR4– (this subset also contained Th9), and CXCR3+CCR6+CCR4– subsets, referred to as Th1/Th17. Th2 were detected on the basis of CCR4 expression in absence of all other chemokine receptors. In addition to the mentioned Th1/Th17 populations, Th 17 cells were found in the subsets of Th17 CXCR3–CCR6+CCR4– and CXCR3–CR6+CCR4+. The latter also contained a Th22 population. Follicular Th cell populations (CXCR5+) consisted of, at least, six different subsets: CXCR3–CCR6–CCR4– (Tfh/Tfh2), CXCR3–CCR6–CCR4+ (Tfh2), CXCR3-CCR6+CCR4–(Tfh17), CXCR3–CCR6+CCR4+ (Tfh17), CXCR3+CCR6–CCR4– (Tfh1) and CXCR3+CCR6+CCR4–(Tfh1/Tfh17). The cells with Th1/Th9 and Th1/Th17 phenotypes dominated among CM (about 13%), whereas their relative abundance within EM increased to 22.37±1.69% and 31.69±1.52%, respectively. The amounts of Th2 were 8.15±0.46% within CM, and only 1.72±0.15% for EM population. For the cells with Th17/Th22 phenotype, these values are 8.07±0.30% and 12.03±0.57%, respectively. The main Tfh subsets were represented among the CM T-helpers: the relative content of Tfh/Tfh2 was 5.79 0.26%, Tfh2, 1.34±0.07%; Tfh17 with CXCR3-CCR6+CCR4– and CXCR3-CCR6+CCR4+ phenotypes made up to 6.22±0.28% and 3.28±0.16%, as well as Tfh1 (7.68±0.31%), and Tfh1/Tfh17 (4.02±0.17%), respectively. Relative content of the mentioned Tfh subsets was decreased > 2-fold within effector memory Th subpopulation. The data obtained may be applied for diagnostics of different immunopathological conditions and could be used as a comparison group in further studies.